2015
DOI: 10.1108/scm-06-2014-0185
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative firms managing perishable products in a complex supply network: an empirical analysis of performance

Abstract: Purpose – This purpose of this study is to provide empirical evidence of how cooperation is related to suppliers’ performance, a relationship that is thought to be affected by the type of customer and the extent to which the market is diversified. It analyzes horticultural exporting firms in southeastern Spain, which are the main suppliers of European markets. Together with their primary customers (large-scale retail companies such as Carrefour, Tesco and Aldi), these firms constitute a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
0
37
0
1
Order By: Relevance
“…In terms of agricultural products, the chain must make maintaining quality and food safety standards of merchandise a top priority throughout the entire process from seed to fork [19]. With respect to perishables, consumers prefer products that are the freshest and have a reasonable price, which requires careful "fine-tuning" of SCM in terms of production planning and scheduling [13], in addition to coordination-collaboration-communication among companies [7,20]. Kumar et al [21] found that coordination strategies are positively correlated with performance.…”
Section: Literature Review: Perishable Supply Chainsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of agricultural products, the chain must make maintaining quality and food safety standards of merchandise a top priority throughout the entire process from seed to fork [19]. With respect to perishables, consumers prefer products that are the freshest and have a reasonable price, which requires careful "fine-tuning" of SCM in terms of production planning and scheduling [13], in addition to coordination-collaboration-communication among companies [7,20]. Kumar et al [21] found that coordination strategies are positively correlated with performance.…”
Section: Literature Review: Perishable Supply Chainsmentioning
confidence: 99%
“…The distribution of agri-food products in Europe is currently undergoing a restructuring process, which affects retailers [6,7]. One of the most prominent changes is the growth of large-scale distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation combined with high debt and low liquidity may raise doubts about the potential resilience of these organizations during prolonged periods of crisis. However, within the fruit and vegetable sector it is quite common for revenues to fall, a fact which constantly exerts stress on companies' results while also increasing competition [36]. This panorama could change as cooperatives start uniting or consolidating more, which has been taking place in recent years, as several second-tier cooperatives now exist which are currently market leaders [37,38].…”
Section: Organization To Gain Market Powermentioning
confidence: 99%
“…Figure 1 shows the importance of the Spanish horticultural export sector, representing the percentage of the Spanish vegetables exportation to each European country, where Germany is the main destination market (32 %). Consumers purchase these products, 70 % at least (Pérez-Mesa and Galdeano-Gómez, 2015), in commercial establishments from huge distribution chains (e.g., Aldi, Carrefour, Edeka, Tesco). These retailers demand high production quality standards from their producers including, among other things, environmentally sustainable practices, high product quality technical standards, and socially sustainable strategies.…”
Section: Introductionmentioning
confidence: 99%